Modern weapons and military equipment for issue 1/2015 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The text is about armaments and military equipment displayed during the parade “March of the Victorious” in Belgrade, 2014. It reflects on most important components of armaments and equipment in the context of bringing the Armed Forces of Serbia up to date, and on the overall impression of the parade as a representative and referent frame of capacities of the Armed Forces for conflicts with possible enemies in all dimensions of war.